Modeling and performance evaluation of a heavy-duty vehicle based on the hydraulic power steering system. (March 2020) - Ahmadi Jeyed, Hamze; Ghaffari, Ali
In most mathematical models that are presented for vehicle performance analysis, the dynamic role of the steering system is ignored and causes the steering effect on the vehicle overall response to be neglected. In this article, the main goal is the performance evaluation of a four-axle heavy-duty vehicle using the modeling and simulation of the vehicle and the hydraulic power steering (HPS) system. For this purpose, using Newton's method, a 20-degrees-of-freedom (20-DOF) nonlinear model of the heavy vehicle is developed, and verified by the TruckSim software results. Then, the comprehensive 4-DOF model of the HPS system, including the steering handwheel angle, rack displacement, and left- and right-hand wheel angles, is presented. Finally, the dynamic model of the heavy-duty vehicle and the HPS system are combined and a 24-DOF dynamic model is simulated in MATLAB software. In order to evaluate the vehicle performance, the simulation on two maneuvers, namely parking and low-speed lane change maneuvers with load and no-load, are carried out. The simulation results demonstrate the desirable performances of the heavy vehicle based on the HPS system on the parking and low-speed maneuvering. Also, the research results provide a better understanding of the vehicle handling considering the nonlinear model of the heavy-duty vehicle based on the HPS system.